Towards the influence of CSR Committees on corporate performance [FRS] - Lopes, A.I. (Research Seminars BRU-IUL, 2021)
The main objectives of this study are to analyse the influence that CSR Committees have on financial and non-financial performance; to test whether that influence is mediated by the role of stakeholder engagement and CSR reporting; and whether it is moderated by the effective date of the European Union Non-financial Reporting Directive. Despite the slight differences between the three EU countries chosen for this study - France, German, and the UK - , we find that the level of engagement with, and reporting to, stakeholders, may act as a channel which strengthens CSR performance, enhancing its role to positively mediate the CSR Committee – non-financial performance relationship. We also find that the presence of CSR Committees boosts that engagement & reporting, without stressing financial performance. Our results also suggest the moderating role the effectiveness of the EU Directive plays with regard to improving direct, and/or indirect mediation through engagement & reporting, and the CSR Committee –financial performance relationship, maintaining the positive impact on non-financial ESG metrics.